Treatment outcomes in psychiatric outpatient care measured by change in the quality of life in Finland - Aalto, Tytti (My University, 2023)
The aim of this study was to assess the effectiveness of routine out-patient care of psychiatric disorders in the Satakunta Hospital district in Finland. The goal was to find out how treatment affects the patients´ quality of life and how background factors and treatment duration influence the outcome. The patients were recruited from among 18 − 65-year-old patients attending all the 4 psychiatric outpatient clinics within Satakunta Hospital District, Finland. The sample consisted of 1) patients making their first-ever visit and 2) patients, who did not have any contact to mental health services in Finland within the preceding three years. Our only two exclusion criteria were a diagnosis of mental retardation and diagnosed neurologic illnesses. 628 subjects took part in the study. We collected comprehensive background data and used 15D questionnaire for health related quality of life (HRQoL), Beck Depression Inventory 1 A (BDI) for depressive symptoms, and AUDIT-5 for alcohol abuse in collecting baseline and follow-up data. Out of all 628 participants, 301 (48%) participants had a clinically significant change in their quality of life measured by 15D during 24-months of follow-up. We found that the change in HRQoL at 3 months was the biggest coefficient and it explained 66,5 % of the change at two year-follow-up. The effects of other variables and background factors on the outcome were not as significant. More research needs to be done for any practical changes to be implemented but we conclude that monitoring patients’ quality of life during psychiatric treatment at an early point could be a good way to predict outcomes.
Keywords: psychiatric outpatient care, health-related quality of life